Antibacterial Effectiveness of Mackerel (Rastrelliger sp) Fish Oil Emulgel against Staphylococcus aureus Bacteria Using Disk-Diffusion Method. - Isnandar; Olivia Avriyanti Hanafiah; Indra Basar Siregar; Salsabila (TALENTA, 2025)
Oral health is a major concern in Indonesia, which is caused by bacteria infections in oral cavity.¹ Bacteria such as Staphylococcus play a crucial role in the development of dental diseases, showing the need for improving oral hygiene to prevent infections.² Therefore, this research aimed to evaluate the effectiveness of mackerel fish oil (Rastrelliger sp.) emulgel against Staphylococcus aureus using the disk diffusion method in an in vitro. The investigation was carried out using an experimental laboratory design with a post-test only control group through the Kirby-Bauer disk diffusion method. The samples consisted of various concentrations of mackerel fish oil emulgel (10, 5, 2.5, 1.25, 0.62, and 0.31%). Clinium® gel 1% was used as a positive control, while gel base was served as a negative control. The formation of inhibition zone diameter after 24 hours of incubation was measured in millimeters (mm) using a vernier caliper. The results showed that mackerel fish oil (Rastrelliger sp.) emulgel had antibacterial activity against Staphylococcus aureus. The mean inhibition zone diameters observed at concentrations 10, 5, 2.5, 1.25, 0.62, and 0.31% were 16.99 mm, 13.23 mm, 10.32 mm, 7.18 mm, and 6.23 mm. Mackerel fish oil (Rastrelliger sp.) emulgel showed effective antibacterial activity against Staphylococcus aureus in an in vitro setting.